Presidential rhetoric as crime control theater: the case of cybercrime - N. Marion; J. B. Hill (Russian Journal of Economics and Law, 2018)
Objective: to comprehensively study the presidential rhetoric as crime control theater.Methods: dialectical approach to the cognition of social phenomena, enabling to analyze them in their historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, and sociological.Results: Presidents have increasingly made criminal justice a part of their public agenda. Much of their political speech on crime and violence focuses on creating the impression of action, even when none is taken. Moreover, if actions are taken, they are ineffective and do not result in significant policy shifts. When presidents give the impression that they are fighting crime, it is often called crime control theater. This is characterized by the use of mythic narratives, a reliance on moral panic, little public dissent, and the ineffectiveness of the policy itself. While many previous studies have demonstrated the importance of crime control theater regarding different criminal justice topics, none have focused on the emerging problems of cybercrime. Scientific novelty: for the first time, the article analyzes the issue of the presidential rhetoric as crime control theater, examines the patterns and trends in presidential rhetoric on cybercrime. The authors use a qualitative content analysis to test the hypothesis that presidents rely on the techniques that comprise crime control theater when discussing cybercrime, in particular, mythic narrative and moral panic. As a result, public fears of cybercrime are allayed but at the same time, any significant action is postponed. The research results have confirmed the proposed hypothesis. Practical significance: the main provisions and conclusions of the article can be used in scientific and pedagogical activity when considering the issues related to the presidential rhetoric as crime control theater.